Design of Electronic Stethoscope and Heartbeat Monitor Using Arduino - Adnan, Taif Firas; Khdaer, Abdullah Naser; Ismail, Abdullah Khalil; Mahmood, Mohammed Mosa (American Journal of Botany and Bioengineering, 2025)
The integration of electronic stethoscope technology with traditional auscultation methods represents a significant advancement in cardiac monitoring. While conventional stethoscopes have been instrumental in medical diagnostics, they suffer from limitations such as ambient noise interference and lack of digital signal processing. This study addresses this gap by designing and implementing an Arduino-based electronic stethoscope and heartbeat monitor that enhances diagnostic precision through digital amplification and real-time data visualization. Using a microcontroller platform, sound sensors, and signal processing algorithms, the system captures, filters, and analyzes heartbeat sounds to improve clarity and usability. Experimental results demonstrate that the proposed device offers superior sound quality and noise reduction compared to traditional models, making it a cost-effective solution for clinical and remote healthcare applications. This study underscores the potential of microcontroller-based medical devices in advancing diagnostic accuracy and accessibility, paving the way for future innovations in digital auscultation.